I must not think bad thoughts : drive-by essays on American dread, American dreams - Dery, Mark, 1959- (University of Minnesota Press, 2012)
From the cultural critic Wired called "provocative and cuttingly humorous" comes a viciously funny, joltingly insightful collection of drive-by critiques of contemporary America where chaos is the new normal. Exploring the darkest corners of the national psyche and the nethermost regions of the self--the gothic, the grotesque, and the carnivalesque--Mark Dery makes sense of the cultural dynamics of the American madhouse early in the twenty-first century. Here are essays on the pornographic fantasies of Star Trek fans, Facebook as Limbo of the Lost, George W. Bush's fear of his inner queer, the theme-parking of the Holocaust, the homoerotic subtext of the Super Bowl, the hidden agendas of IQ tests, Santa's secret kinship with Satan, the sadism of dentists, Hitler's afterlife on YouTube, the sexual identity of 2001's HAL, the suicide note considered as a literary genre, the surrealist poetry of robot spam, the zombie apocalypse, Lady Gaga, the Church of Euthanasia, toy guns in the dream lives of American boys, and the polymorphous perversity of Madonna's big toe. Dery casts a critical eye on the accepted order of things, boldly crossing into the intellectual no-fly zones demarcated by cultural warriors on both sides of America's ideological divide: controversy-phobic corporate media, blinkered academic elites, and middlebrow tastemakers. Intellectually omnivorous and promiscuously interdisciplinary, Dery's writing is a generalist's guilty pleasure in an age of nanospecialization and niche marketing. From Menckeneaque polemics on American society and deft deconstructions of pop culture to unflinching personal essays in which Dery turns his scalpel-sharp wit on himself, I must not think bad thoughts is a head-spinning intellectual ride through American dreams and American nightmares.